Anomie and Adult Crime - Collins, Angela M. (Journal of developmental and life-course criminology, 2021)
The field of life course and developmental criminology has advanced our knowledge with research on several topics, including age of onset, persistence and continuity, desistance, trajectories of delinquency and crime, correlates of delinquency and crime at different ages and stages of the life course, and correlates of these phenomena, but it has not done extensive, full theory tests of theories for different stages of the life course. The present study tests anomie/strain theory for adult crime and compares the results to previous results for anomie theory in adolescence and early adulthood using longitudinal data on a national probability sample that follows respondents from early adolescence to middle adulthood. Although anomie theory appears to have originally been a theory intended to explain adult crime, the findings indicate that it does better at explaining middle adolescent and young adult illicit substance use and other criminal or delinquent behaviors. These results suggest that testing full theories, not just individual hypotheses about correlates, may improve our understanding of the evolving etiology of illegal behavior over the life course.